2013
DOI: 10.1021/jp402946c
|View full text |Cite
|
Sign up to set email alerts
|

A Strongly Absorbing Class of Non-Natural Labels for Probing Protein Electrostatics and Solvation with FTIR and 2D IR Spectroscopies

Abstract: A series of non-natural infrared probes is reported that consist of a metal-tricarbonyl modified with a -(CH2)n- linker and cysteine-specific leaving group. They can be site-specifically attached to proteins using mutagenesis and similar protocols for EPR spin labels, which have the same leaving group. We characterize the label’s frequencies and lifetimes using 2D IR spectroscopy in solvents of varying dielectric. The frequency range spans 10 cm−1, and the variation in lifetimes ranges from 6 to 19 ps, indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
77
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(79 citation statements)
references
References 69 publications
2
77
0
Order By: Relevance
“…32,[49][50][51] However, it should be noted that the variation in the amide I vibrational lifetimes of proteins is generally small. For example, a change of ∼50% was observed between a solvated and a hydrophobic site in the M2 tetramer.…”
Section: B 2d Ir Spectramentioning
confidence: 99%
“…32,[49][50][51] However, it should be noted that the variation in the amide I vibrational lifetimes of proteins is generally small. For example, a change of ∼50% was observed between a solvated and a hydrophobic site in the M2 tetramer.…”
Section: B 2d Ir Spectramentioning
confidence: 99%
“…Finally we tested the 2DIR setup based on TWINS. Figure 5 shows the 2DIR spectra of a 50-micrometer-thick sample of a Rhenium carbonyl complex in dimethyl sulfoxide, which was recently introduced as an IR-label for proteins [31,32].Two identical pump-pulses were created by the birefringent wedges and the delay t 1 between them (the coherence time) was scanned continuously from −0.3 to 3 ps. The 2D spectrum is given by the FT of the probe beam intensity along t 1 , and the frequency axis defined by this FT is the horizontal axis in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The only difference is the vastly disparate timescales probed by the two methods -picoseconds versus milliseconds -, which refers to the "direct time resolution" inherent to both techniques. In the context of protein dynamics, 2D IR spectroscopy has been applied to investigate the structure of membrane peptides [21,22], fibril formation [23,24], the structural flexibility of enzyme active sites [25], ligand migration in heme proteins [26], ligand binding [27,28], and the dynamics of the protein hydration shell [29,30], to list just a few examples. Recent reviews can be found in Refs.…”
Section: Advancing the Sensitivitymentioning
confidence: 99%
“…The protein should have only one of these amino acids at the desired position, and in this regard, Met is advantageous as it is relatively rare in natural proteins, whereas His is often crucial for their function. Note that we have disregarded cysteine as another possible anchor point for a label [29], since we want to keep that amino acid free for adding other functionalities, such as a photoswitch [6,8,12,13,59] used to initiate a non-equilibrium process (see the example highlighted below). We reiterate that being able to initiate a non-equilibrium process is a prerequisite to extend the accessible time window beyond the vibrational lifetime of the label.…”
Section: Advancing the Selectivitymentioning
confidence: 99%